0260 Does multi-dimensional impulsivity mediate the relationship between poor sleep health and depressive symptoms in late adolescents?. (25th May 2022) - Kwon, Misol; Seo, Young; Hasler, Brant
Abstract: Introduction: Abundant evidence links poor sleep health to problems with mental health, including depression. Poor sleep is also associated with deficits in impulse control, which have been linked in turn to depressive symptoms, perhaps most notably suicidality. However, whether impulsivity may partly account for the relationship between poor sleep health and depressive symptoms remains understudied. Here, we examined whether multi-dimensional impulsivity mediated the relationship between sleep health and depressive severity in a sample of late adolescent drinkers. Methods: The sample consisted of 96 late adolescents (58.3% female; mean age 17.6 years) reporting regular alcohol use. Daily sleep duration, timing (sleep midpoint), and continuity (efficiency) were assessed using wrist actigraphy. Five facets of impulsivity (namely, negative urgency, lack of perseverance, positive urgency, lack of premeditation, and sensation seeking) were assessed via the UPPS-P Impulsive Behavior scale. Depressive symptoms were assessed via the Inventory of Depressive Symptomatology (IDS-SR-30). Results: Mediation analyses showed that the associations between sleep health and depression severity were not mediated through impulsivity. However, results indicated that negative urgency and lack of perseverance were associated with increased severity in depression (B = .75, 95% CI, .27, 1.23 for negative urgency; B = .55, 95% CI, .12, .97 for lack of perseverance), whereas lack of premeditation was inversely associated with depression severity (B = -.72, 95% CI, -1.15, -.29). Conclusion: Our findings suggest that sleep duration, timing and continuity were not related to any of the multi-dimensional impulsivity components used. However, findings show that negative urgency and lack of perseverance were related to heightened depressive severity but lack of premeditation was known to decrease depression severity. Further analysis may be needed to examine the mediational paths in the associations between sleep health and depressive symptoms, for example, by using latent constructs of sleep health and impulsivity, thus taking measurement errors into account. Support (If Any): This research was funded by R01 AA026249 (Hasler) by the National Institute of Alcohol Abuse and Alcoholism; and Sleep Research Society Mentor Mentee Award (Kwon).